Gold nanoplatform for near-infrared light-activated radio-photothermal gas therapy in breast cancer - Zuo, Shuting; Wang, Zhenyu; Zhao, Liping; Wang, Jing (Frontiers in Bioengineering and Biotechnology, 2023)
Radiotherapy, as one of the most common treatments for triple-negative breast cancer (TNBC), suffers from an unsatisfactory therapeutic outcome due to radiation resistance in tumor tissues. There is an urgent need to seek a synergistic strategy to increase therapeutic responses and prolong the patient survival. Herein, we constructed a gold nanocages to load a hyperpyrexia-sensitive nitric oxide (NO) donor, thiolate cupferron for integrating extrinsic radio-sensitization, local photothermal therapy and NIR-activated NO gas therapy. The formed nanoplatform (GNCs@NO) showed a high photothermal conversion efficiency, which not only induce the death of cancer cells, but also facilitate the rapid NO release in tumor tissues. In vitro and in vivo assay results confirmed the radio-sensitization efficacy of GNCs@NO. Importantly, the released NO reacted with the reactive oxide species (ROS) induced by radiotherapy to produce the more toxic reactive nitrogen species (RNS), exerting synergistic effect to improve anticancer efficacy. Thus, GNCs@NO displayed an excellent combination therapy along with low adverse effects. Overall, our work offers a promising nanoplatform for the radio/photothermal/gas treatments of TNBC.